Physicochemical, functional and antinutritional properties of starches from Caladium bicolor and Dioscorea dumentorum - Uwem, Ifiok Nseobong; Ita, Basil Nse (European Journal of Chemistry, 2019)
Starch samples from the wild species of cocoyam (Caladium bicolor (Aiton) Vent.) and three leaf yam (Dioscorea dumentorum (Kunth) Pax.) found abundantly in the south and eastern regions of Nigeria, were characterized for their physicochemical, functional and antinutrient properties. C. bicolor had higher amylose (17.68%), carbohydrate (83.57%) and ash (2.85%) than D. dumentorum. Moisture, crude lipid, protein and fibre ranged between 7.56 to 10.29%, 0.12 to 0.15%, 0.11 to 0.13%, and 2.85 to 3.39%, respectively. The starches exhibited promising functional properties with D. dumentorum having higher dispersibility (64.85%), solubility (73.99%) and oil absorption capacity (2.15 g/g). Onset (To), midpoint (Tm), and conclusion (Tc) gelatinization temperatures ranged between 63 to 79 °C. Peak, breakdown and setback viscosity were higher in D. dumentorum than C. bicolor. Moisture sorption behavior indicated increased hygroscopy with exposure time. The starches had high antinutrient levels, with D. dumentorum having higher levels of HCN and oxalates. In addition, infrared (IR) spectra of both starches were similar. Taken together, these properties suggest the suitability of these starches for non-food applications due to their high antinutrient contents.